EMPOWERING FEMALE LEADERSHIP: ORGANIZATIONAL MANAGEMENT STRATEGIES AT DAYAH TERPADU ULUMUDDIN FOR DEVELOPING STUDENT LEADERS - Jannah, Icha Rauzatul; Almuhajir, Almuhajir (Managere: Indonesian Journal of Educational Management, 2024)
This study offer approach new in development leadership female students through management organization students at integrated pesantren, with focus on integration religious values and skills leadership practical. This aim For analyze effectiveness management organization student in form personality and leadership female students at pesatren. The method used in this research is a qualitative approach with data collection techniques through in-depth interviews, observation and documentation analysis. The research subjects consisted of student organization administrators, teachers and female students. The results of the research show that student organization planning at pesantren includes the formation of a clear organizational structure, understanding the schedule of student activities, as well as implementing standard operational procedures and sanctions. The consistent implementation of these programs has succeeded in forming female students' personalities who are disciplined and organized. Apart from that, the trustworthy and democratic leadership style applied by integrated santri leadership organization, with support from the care team, is effective in forming student leadership with character and responsibility. This research is expected to provide scientific references to continue to develop and update leadership programs and strengthen cooperation with other institutions that share the same vision. In addition, there needs to be periodic evaluation to ensure the effectiveness of the program and adjust it to the evolving needs of female students.